SIMPLE BOOKKEEPING TRAINING AND HALAL CERTIFICATION MANAGEMENT FOR SMEs IN GAMPONG LAMPULO, KUTA ALAM SUBDISTRIC, BANDA ACEH - Syamsidar Syamsidar; Emmi Suryani NST; Surna Lastri; Tuwisna Tuwisna (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2023)
MSMEs (Micro, Small and Medium Enterprises) are the foundation of the Indonesian economy. Indonesia is unique in its economic system, namely an economic system that is based on economic democracy or people's economy. It can be interpreted that the Indonesian economic system has unique characteristics that differentiate it from the economic systems of other countries. MSMEs have a very important role in the economy in Banda Aceh City and MSMEs also absorb a lot of labor. The city of Banda Aceh also still has homework (homework), namely to reduce the poverty rate, the existence of MSMEs can be one solution in alleviating unemployment and poverty in the city of Banda Aceh. One of the MSME locations that is currently developing is in Gampong Lampulo, Kuta Alam District, Banda Aceh City, where local residents are starting to develop MSME businesses such as wooden fish processing businesses (Keumamah), spice processing, food processing, and several other businesses. As we all know, the existence of Gampong Lampulo, which is located on the coast, is a place where fishing boats dock and is also a place for fish auctions, so that fresh fish as a basic ingredient for public affairs is always available. Bookkeeping of financial transactions is one of the important tasks in carrying out or recording business transactions. This bookkeeping is often rarely carried out by Micro, Small and Medium Enterprises (MSMEs) because of limited information in the field of accounting and Micro, Small and Medium Enterprises (MSMEs) focus only on how to do marketing. The MUI Halal Certificate is a written fatwa from the Indonesian Ulema Council which states that a product is halal in accordance with Islamic law.  Keywords: Simple Bookkeeping, Halal Certification, MSMEs